Iatrogenic acid‐induced gingival recession during crown cementation: A case report. (29th January 2021) - Kofina, V; An, H; Rawal, SY
Abstract: Accidental contact of various chemicals in dentistry may cause damage to the gingiva. A male patient presented for a full mouth rehabilitation with ceramic crowns. The patient underwent the steps of ceramic crown preparation uneventfully. At the time of crown delivery, cotton rolls were placed in several vestibular areas for isolation. They were regularly changed during different steps of etching and cementation process, which included the use of Multilink Primer B (Ivoclar Vivadent™). On removal of the cotton roll in the area of upper right canine, the gingival tissues appeared blanched and grayish white. The cotton roll was found to have absorbed some etching material in it. As the patient was asymptomatic, he was dismissed. Two weeks later, the patient presented with inflammation and gingival recession in the same area. Initially, he was treated palliatively, and subsequently, he received a connective tissue graft on the upper right canine. This case report showed that acid etching material used during the prosthodontic cementation may have caused a gingival recession, which was successfully treated with tunnel flap and connective tissue graft. Optimal isolation of the operative field should be performed to avoid this problem.